Narrowband purple light material and application thereof in organic light emitting diode
By designing a multi-resonance structure of narrowband purple light materials to be used for the luminescent layer of organic electroluminescent diodes, the problems of high difficulty, low yield and poor efficiency of multi-resonance materials are solved, and narrowband luminescence and high-efficiency charge transmission are achieved , improves the thermal stability and luminous efficiency of the device.
Patent Information
- Application Number
- CN202411253123.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing multi-resonance materials have high difficulty in synthesis, low yield, wide fluorescence spectrum and poor efficiency.
A narrow band violet material was designed, with a chemical structure including specific R1-R6 substituents and heteroaryl groups. A multi-resonance framework was constructed through aromatic nucleophilic substitution and intramolecular Heck coupling to form a C-N multi-resonance structure based on carbazolyl , used to prepare a light emitting layer of an organic electroluminescent diode.
It realizes narrow spectrum band luminescence, improves the thermal stability and charge transfer performance of the device, reduces the difficulty of synthesis and production costs, and improves the luminescence efficiency and stability.
Smart Images

Figure CN119119060A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic light-emitting materials, and in particular to a narrow-band violet light material and an organic electroluminescent diode. Background Art
[0002] As the world enters the information age, liquid crystal display technology can no longer meet people's higher requirements for display. In order to achieve a better experience, new wearable smart devices, portable electronic devices, high-end medical display devices, etc. all require more advanced display technology. Therefore, it is urgent to develop new display technologies that are ultra-light and ultra-thin, with high color saturation and low energy consumption. Organic light-emitting diodes (OLED) can almost meet all the requirements of new displays. Compared with the point-emitting properties of inorganic light-emitting diodes (LEDs), the surface-emitting properties of OLEDs make it easier to achieve large-area luminescence or large-area flat-panel displays. OLED has incomparable advantages in the production of shadowless lamps and flexible display devices. Therefore, after only more than 30 years of development, OLED has made breakthroughs in both basic research and practical applications. At present, almost all high-end models of smartphones on the market use OLED displays. Although it has obvious advantages in the fields of display and lighting, OLED is still plagued by high production costs, unsatisfactory luminous efficiency of materials and device stability. To achieve a breakthrough, it is necessary to start from the root of luminescent materials.
[0003] Organic light-emitting diodes (OLEDs) are a successful light-emitting device that can realize efficient electroluminescent (EL) devices through engineering luminescent materials. They can cover all visible colors, and red, green and blue OLEDs are being used in commercial products. Even near-infrared OLEDs have been studied and are being actively developed. The use of chemical modification methods to prepare multi-resonance materials with narrow emission peak widths provides a more convenient and efficient way. Multi-resonance materials are organic molecules in which atoms or groups with opposite electronegativity are embedded in polycyclic aromatic hydrocarbons. Due to the opposite multi-resonance effect, the frontier molecular orbital (FMO) is compensated by the same atoms or groups. This type of material has the advantages of narrow-band luminescence, strong thermal stability, good charge transfer performance and high efficiency. The multi-resonance materials that have been proposed are mostly based on BN(O) multi-resonance small molecules and carbonyl-N multi-resonance small molecules. There are problems such as high synthesis difficulty and low yield, or wide fluorescence spectrum and poor efficiency. Summary of the invention
[0004] The technical problem solved by the present invention is to address at least one of the following aspects: high difficulty in synthesizing multi-resonance materials, low yield, wide fluorescence spectrum and poor efficiency.
[0005] In order to solve the above problems, the present invention provides a narrow-band violet light material, and the chemical structure of the narrow-band violet light material is shown in the following formula:
[0006]
[0007] wherein R1-R6 are each independently one of hydrogen, an alkyl group having 1 to 10 carbon atoms, a cyano group, an aryl group having 5 to 25 carbon atoms and containing at least one substituent or being unsubstituted, or a heteroaryl group having 5 to 25 carbon atoms and containing at least one substituent or being unsubstituted;
[0008] The substituent is at least one selected from alkyl groups having 1 to 10 carbon atoms.
[0009] In some specific narrow-band violet materials, R1-R6 are independently one of hydrogen, an alkyl group having 1-10 carbon atoms, a cyano group, a C5-C15 phenyl group having at least one substituent or no substituent, and a C5-C15 heteroaryl group having at least one substituent or no substituent.
[0010] The substituent is at least one selected from alkyl groups having 1 to 10 carbon atoms.
[0011] The heteroatom on the heteroaryl group is selected from at least one of O, N, and S.
[0012] In some specific narrow-band violet materials, R1-R6 are independently hydrogen, an alkyl group having 1-6 carbon atoms, a C5-C15 aryl group having at least one substituent or no substituent, or a C5-C15 heteroaryl group having at least one substituent or no substituent.
[0013] The substituent is at least one selected from alkyl groups having 1 to 6 carbon atoms.
[0014] The heteroatom on the heteroaryl group is N. In some specific narrow-band violet materials, R1-R6 are independently hydrogen, an alkyl group having 1-5 carbon atoms, a phenyl group having at least one substituent or no substituent, a pyridyl group having at least one substituent or no substituent, or a carbazole group having at least one substituent or no substituent.
[0015] The substituent is at least one selected from alkyl groups having 1 to 5 carbon atoms.
[0016] In some specific narrow-band ultraviolet materials, R1-R6 are independently hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, phenyl containing at least one substituent or no substituent, pyridyl containing at least one substituent or no substituent, or carbazole containing at least one substituent or no substituent.
[0017] The substituents are each independently at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl, isopentyl, and neopentyl.
[0018] In some specific narrow-band violet materials, R1-R6 are independently hydrogen, tert-butyl, or a carbazole group containing at least one substituent or containing no substituent.
[0019] The substituent is tert-butyl.
[0020] Furthermore, the narrow-band violet light material is selected from the following structures:
[0021]
[0022] Furthermore, the steady-state fluorescence spectrum of the narrow-band violet light material in toluene solution ranges from 380 to 800 nm, and the half-peak width is less than or equal to 40 nm.
[0023] The present invention also provides an organic electroluminescent diode, wherein the light-emitting layer of the diode comprises at least one of the above-mentioned narrow-band violet light materials.
[0024] Some specific technical solutions, the organic electroluminescent diode includes an anode layer, a hole injection layer, at least one hole transport layer, a light-emitting layer, at least one electron transport layer, an electron injection layer and a cathode layer stacked in sequence, and the light-emitting layer includes the narrow-band violet light material described above.
[0025] Furthermore, in the light-emitting layer, the mass percentage of the narrow-band violet light material is 0.1% to 20%.
[0026] Furthermore, in the light-emitting layer, the mass percentage of the narrow-band violet light material is 0.1% to 10%.
[0027] Furthermore, in the light-emitting layer, the mass percentage of the narrow-band violet light material is 1% to 10%.
[0028] Furthermore, the thickness of the light-emitting layer is 10 nm to 200 nm.
[0029] Furthermore, the thickness of the light-emitting layer is 10 nm to 100 nm.
[0030] Furthermore, the thickness of the light-emitting layer is 10 nm to 50 nm.
[0031] The organic small molecule luminescent material of the present invention has the following characteristics:
[0032] 1. The molecular system is novel, has a large expansion space and a narrow half-peak width of the spectrum.
[0033] 2. The narrow-band violet material of the present invention is easy to synthesize, and the raw materials are cheap and easily available. At the same time, it has a rigid skeleton structure and a planar structure, which reduces the vibration relaxation during the radiation transition process, gives the molecule good thermal stability and the luminescent film good charge transfer performance, which is beneficial to improving the efficiency and stability of the device.
[0034] 3. The matrix of the organic small molecule luminescent material of the present invention is a CN multi-resonance structure based on carbazole. Compared with the DA or D-π-A structure of the thermally activated delayed fluorescence (TADF) material, it can well separate the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO), greatly reducing the excited state configuration transition. The whole molecule therefore exhibits narrow-band luminescence. At the same time, compared with the BN multi-resonance structure that must rely on extremely dangerous alkyl lithium reagents and low-yield introduction of B atoms, the present invention only needs to construct a multi-resonance skeleton through aromatic nucleophilic substitution and intramolecular Heck coupling or dehydrogenation coupling, which is safer, more convenient and economical.
[0035] The advantages of the organic light-emitting diode described in the present invention over the prior art are the same as the advantages of the narrow-band violet light material over the prior art, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The thermogravimetric curves of SSCz-C2HDC and SSCz-C2H-1 in Examples 1-2 of the present invention.
[0037] Figure 2 The UV-visible absorption spectrum of the compound SSCz-C2HDC in Example 1 of the present invention in n-hexane, toluene, dichloromethane, tetrahydrofuran, acetonitrile and methanol solutions.
[0038] Figure 3 The UV-visible absorption spectrum of the compound SSCz-C2H-1 in Example 1 of the present invention in n-hexane, toluene, dichloromethane, tetrahydrofuran, acetonitrile and methanol solutions.
[0039] Figure 4 The photoluminescence spectra of the compound SSCz-C2HDC in Example 1 of the present invention in n-hexane, toluene, chloroform, tetrahydrofuran, acetonitrile and methanol solutions are shown in FIG.
[0040] Figure 5 The photoluminescence spectrum of the compound SSCz-C2H-1 in Example 1 of the present invention in n-hexane, toluene, dichloromethane, tetrahydrofuran, acetonitrile and methanol solutions is shown.
[0041] Figure 6 1 is the structure and energy level diagram of the organic light emitting diode device according to Example 11 of the present invention.
[0042] Figure 7 This is a current density-voltage-brightness curve of the organic light emitting diode of Example 12 of the present invention.
[0043] Figure 8 The brightness-external quantum efficiency curves of the organic light emitting diodes of Examples 11 and 12 of the present invention are shown.
[0044] Fig. 9 The electroluminescence spectra of the organic electroluminescent diodes of Examples 11 and 12 of the present invention are shown.
[0045] Fig.10 It is the general structural formula of the narrow-band violet light material of the present invention. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0047]
[0048] Example 1: The synthesis steps of narrow-band violet material compounds SSCz-C2HDC, SSCz-C2H-1, and SSCz-C2H-2 are as follows:
[0049] Step 1: Add the raw material 1-1 (5.30 g, 18.98 mmol), 1,4-dibromo-2,3-difluorobenzene (2.0 g, 5.42 mmol), and cesium carbonate (12.37 g, 37.96 mmol) to a 250 ml three-necked flask, then add 40 ml of N, N-dimethylformamide (DMF), evacuate and replace nitrogen three times, and then stir and react for 12 hours at 75 ° C in a nitrogen atmosphere. After cooling, add a large amount of water, precipitate the product, and then filter it, recrystallize it with dichloromethane and methanol to obtain 4.31 g of a white powdery crude product of 1-2, with a yield of 69.30%.
[0050] Step 2: Add the dried compound 1-2 (3.0 g, 2.62 mmol), palladium acetate (0.29 g, 1.31 mmol), triphenylphosphine (0.69 g, 2.62 mmol), potassium carbonate (3.61 g, 26.15 mmol), and tetrabutylammonium bromide (2.53 g, 7.85 mmol) into a 250 ml three-necked flask, and then add 50 ml of dimethylacetamide (DMAc), evacuate and replace nitrogen three times, and then stir and react under reflux conditions in a nitrogen atmosphere for 12 h. After cooling, a large amount of water was added to precipitate a dark green solid, which was then washed with a large amount of ethanol, separated and purified by column chromatography, and dried to obtain a light yellow powder SSCz-C2HDC with a weight of 0.55 g and a yield of 23.3%. A light yellow powder SSCz-C2H-1 with a weight of 0.75 g and a yield of 31.5% was obtained. A light yellow powder SSCz-C2H-2 with a weight of 0.52 g and a yield of 21.8% was obtained.
[0051] The NMR spectrum of compound SSCz-C2HDC is: 1H MMR (400MHz, Chloroform-d) δ8.40 (s, 1H), 8.36 (s, 2H), 8.16 (s, 2H), 8.08 (d, 2H), 7.98 (s, 2H), 7.68 (d, 2H), 7.30 (d, 2H), 7.01 (d, 2H), 6.56 (s, 2H), 1.41-1.44 (d, 36H), 1.05 (s, 18H). 13C NMR (400MHz, Chloroform-d) rm-d) δ 146.77, 145.57, 144.58, 143.28, 139.34, 138.08, 137.14, 130.56, 124.18, 123.80, 123.61, 122.64, 120.00, 119.79, 117.56, 116.71, 116.43, 116.01, 111.80, 111.55, 35.58, 35.02, 34.87, 32.23, 31.95, 31.78, MALDI-TOF: found by 905.5643.
[0052] Example 2: The synthesis steps of narrow-band violet material compounds 2-3a, 2-3b, and 2-3c are as follows:
[0053] Step 1: Add the raw material 2-1 (6.10 g, 18.98 mmol), 1,4-dibromo-2,3-difluorobenzene (2.0 g, 5.42 mmol), and cesium carbonate (12.37 g, 37.96 mmol) to a 250 ml three-necked flask, then add 40 ml of N, N-dimethylformamide (DMF), evacuate and replace nitrogen three times, and then stir and react for 12 hours at 75 ° C in a nitrogen atmosphere. After cooling, add a large amount of water, precipitate the product, and filter it, recrystallize it with dichloromethane and methanol to obtain 5.23 g of a white powdery crude product of 2-2, with a yield of 75.8%.
[0054] Step 2: Add the dried compound 2-2 (3.0 g, 2.36 mmol), palladium acetate (0.26 g, 1.18 mmol), triphenylphosphine (0.62 g, 2.36 mmol), potassium carbonate (3.26 g, 23.59 mmol), and tetrabutylammonium bromide (2.29 g, 7.08 mmol) into a 250 ml three-necked flask, and then add 50 ml of dimethylacetamide (DMAc), evacuate and replace nitrogen three times, and then stir the reaction under reflux conditions in a nitrogen atmosphere for 12 h. After cooling, a large amount of water was added to precipitate a dark green solid, which was then washed with a large amount of ethanol, separated and purified by column chromatography, and dried to obtain a light yellow powder 2-3a with a weight of 0.88 g and a yield of 23.3%. A light yellow powder 2-3b with a weight of 0.60 g and a yield of 24.8% was obtained. A light yellow powder 2-3c with a weight of 0.66 g and a yield of 27.2% was obtained.
[0055] Example 3: The synthesis steps of narrow-band violet material compounds 3-3a, 3-3b, and 3-3c are as follows:
[0056] Step 1: Add the raw material 3-1 (9.45g, 18.98mmol), 1,4-dibromo-2,3-difluorobenzene (2.0g, 5.42mmol), cesium carbonate (12.37g, 37.96mmol) to a 250ml three-necked flask, then add 40ml N, N-dimethylformamide (DMF), evacuate and replace nitrogen three times, and then stir and react for 12h at 75°C in a nitrogen atmosphere. After cooling, add a large amount of water, precipitate the product, filter it, and recrystallize it with dichloromethane and methanol to obtain 6.79g of a white powdery crude product of 3-2 with a yield of 69.5%.
[0057] Step 2: Add the dried compound 3-2 (3.0 g, 1.67 mmol), palladium acetate (0.19 g, 0.83 mmol), triphenylphosphine (0.44 g, 1.67 mmol), potassium carbonate (2.30 g, 16.65 mmol), and tetrabutylammonium bromide (1.61 g, 5.00 mmol) into a 250 ml three-necked flask, and then add 50 ml of dimethylacetamide (DMAc), evacuate and replace nitrogen three times, and then stir the reaction under reflux conditions in a nitrogen atmosphere for 12 hours. After cooling, a large amount of water was added to precipitate a dark green solid, which was then washed with a large amount of ethanol, separated and purified by column chromatography, and dried to obtain a light yellow powder 3-3a with a weight of 0.61 g and a yield of 23.6%. A light yellow powder 2-3b with a weight of 0.85 g and a yield of 32.6% was obtained. A light yellow powder 2-3c with a weight of 0.65 g and a yield of 24.8% was obtained.
[0058] Example 4: The compounds SSCz-C2HDC and SSCz-C2H-1 in Example 1 were heated at a rate of 10°C / min in the range of 50-700°C under N2 protection, and the thermogravimetric curves were measured using a differential scanning calorimeter model DSC 204. Figure 1 It can be seen that the temperature at which the compound SSCz-C2HDC decomposes by 5% is 301°C, and the temperature at which the compound SSCz-C2H-1 decomposes by 5% is 295°C, indicating that the two materials have good thermal stability.
[0059] Example 5: UV-visible light absorption performance test of the compound SSCz-C2HDC in Example 1 in different solutions. The compound SSCz-C2HDC was dissolved in n-hexane, toluene, dichloromethane, tetrahydrofuran, acetonitrile and methanol solutions (all at a concentration of 10 -5 M), and use UV-visible absorption spectrometer to test its UV-visible light absorption performance in different solutions. Figure 2 As shown, with the increase of solvent polarity, the UV-visible absorption spectrum of compound SSCz-C2HDC did not show obvious changes.
[0060] Example 6: UV-visible light absorption performance test of the compound SSCz-C2H-1 in Example 1 in different solutions. The compound SSCz-C2H-1 was dissolved in n-hexane, toluene, dichloromethane, tetrahydrofuran, acetonitrile and methanol solutions (all with a concentration of 10 -5 M), and use UV-visible absorption spectrometer to test its UV-visible light absorption performance in different solutions. Figure 3 As shown, the UV-visible absorption spectrum of compound SSCz-C2H-1 did not show obvious changes with the increase of solvent polarity.
[0061] Example 7: Photoluminescence performance test of the compound SSCz-C2HDC in Example 1 in different solutions. The compound SSCz-C2HDC was dissolved in n-hexane, toluene, chloroform, tetrahydrofuran, acetonitrile and methanol solutions (all with a concentration of 10 - 5 M), and the photoluminescence spectra in different solutions were tested using a fluorescence spectrophotometer. Figure 4 As shown, the solution fluorescence of the compound SSCz-C2HDC in different solvents is all in the near-ultraviolet violet region, and the half-peak width of the fluorescence spectrum is very narrow, which has the typical characteristics of multi-resonance materials.
[0062] Example 8: Photoluminescence performance test of the compound SSCz-C2H-1 in Example 1 in different solutions. The compound SSCz-C2H-1 was dissolved in n-hexane, toluene, dichloromethane, tetrahydrofuran, acetonitrile and methanol solutions (all with a concentration of 10 -5 M), and the photoluminescence spectra in different solutions were tested using a fluorescence spectrophotometer. Figure 5 As shown, the solution fluorescence of compound SSCz-C2H-1 in different solvents is all in the near-ultraviolet region, and the half-peak width of the fluorescence spectrum is very narrow, which has the typical characteristics of multi-resonance materials.
[0063] Example 9: The steps for preparing the organic light emitting diode in this example are as follows:
[0064] Step 9-1, clean the conductive ITO glass with a cleaning agent, dry it, treat it with ozone for 30 minutes, and transfer it to a glove box filled with nitrogen for later use;
[0065] Step 9-2, under high vacuum (1 x 10 -6 Pa) environment, NPB hole injection layer, TCTA electron blocking layer, mCP electron blocking layer, light-emitting layer, TSPO1 hole blocking layer, TPBi electron transport layer, LiF electron injection layer and Al cathode layer purchased from Xi'an Yuri Solar Energy Company are sequentially deposited on the ITO anode layer; wherein the light-emitting layer includes main materials mCBP (48.5%) and TSPO1 (48.5%), and guest material SSCz-C2HDC (3%). The structure of the organic electroluminescent diode device thus prepared is: ITO / NPB (75nm) / TCTA (5nm) / mCP (5nm) / light-emitting layer (20nm) / TSPO1 (5nm) / TPBi (20nm) / LiF (1nm) / Al (200nm);
[0066] Step 9-3, testing of OLED devices: After the overall production of the device is completed, the vacuum chamber of the vacuum coating machine needs to cool down naturally for 30 minutes, and then turn off the molecular pump and mechanical pump in turn. Finally, take out the device from the vacuum chamber, and use the spectrophotometer CS200 and the power supply meter Keithley 236 to test the device voltage-current-brightness data. Then use the spectrophotometer PR705 to test the device's electroluminescence spectrum (EL) and color coordinates (CIE). Use the above data to calculate the current density, current efficiency, power efficiency and external quantum efficiency of the device under different driving voltages, and obtain key performance data such as current density-voltage-brightness, current density-external quantum efficiency and electroluminescence spectrum.
[0067] Figure 6 1 is the device structure and energy level diagram of the above embodiment. Figure 7 The current density-voltage-brightness curve of the organic light-emitting diode obtained in Example 9 is shown in the figure. It can be seen from the figure that the turn-on voltage of the organic light-emitting diode in Example 9 is 4V; the current density reaches 49.8mA / cm 2 ; Maximum brightness reaches 131.7cd / m 2 .
[0068] Figure 8 The graph is a brightness-external quantum efficiency curve of the organic light emitting diode of Example 9. As can be seen from the graph, the maximum external quantum efficiency of the organic light emitting diode of Example 9 is 2.33%, which is a diode device with relatively high efficiency among near-ultraviolet devices.
[0069] Fig. 9 The electroluminescence spectrum of the organic electroluminescent diode of Example 9 is shown in the figure. As can be seen from the figure, the maximum emission wavelength and half-peak width of the electroluminescent organic electroluminescent diode of Example 9 are 404nm and 14nm respectively, which is a very good narrow-band luminescent body. It can be seen that SSCz-C2HDC is a good material option for high-definition display technology.
[0070] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A narrow-band violet material, characterized in that: The chemical structure of the narrow-band violet material is: Wherein, R1-R6 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, a cyano group, a C5-C25 aryl group having at least one substituent or no substituent, or a C5-C25 heteroaryl group having at least one substituent or no substituent; The substituent is selected from an alkyl group having 1 to 10 carbon atoms; The heteroatom on the heteroaryl group is selected from at least one of N, O and S.
2. The narrow-band violet material according to claim 1, characterized in that: R1-R6 are each independently hydrogen, an alkyl group having 1 to 10 carbon atoms, a cyano group, a C5-C15 aryl group having at least one substituent or no substituent, or a C5-C15 heteroaryl group having at least one substituent or no substituent; The substituent is selected from at least one of alkyl groups having 1 to 10 carbon atoms; The heteroatom on the heteroaryl group is N.
3. The narrow-band violet material according to claim 2, characterized in that: R1-R6 are each independently hydrogen, an alkyl group having 1 to 6 carbon atoms, a C5-C15 aryl group having at least one substituent or no substituent, or a C5-C15 heteroaryl group having at least one substituent or no substituent; The substituent is at least one selected from alkyl groups having 1 to 6 carbon atoms.
4. The narrow-band violet material according to claim 3, characterized in that: R1-R6 are each independently hydrogen, an alkyl group having 1 to 5 carbon atoms, a phenyl group having at least one substituent or no substituent, a pyridyl group having at least one substituent or no substituent, or a carbazolyl group having at least one substituent or no substituent; The substituent is at least one selected from alkyl groups having 1 to 5 carbon atoms.
5. The narrow-band violet material according to claim 4, characterized in that: R1-R6 are hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, or carbazolyl containing at least one substituent or no substituent; The substituent is selected from at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl, isopentyl and neopentyl.
6. The narrow-band violet material according to claim 1, characterized in that: The material is selected from the following structures:
7. The narrow-band violet material according to any one of claims 1 to 6, characterized in that: The wavelength range of the steady-state fluorescence spectrum of the narrow-band violet light material in a toluene solution is 380-800 nm, and the half-peak width is less than or equal to 40 nm.
8. An organic light emitting diode, characterized in that: The light-emitting layer of the diode comprises at least one of the materials described in any one of claims 1 to 6.
9. The organic light emitting diode according to claim 8, characterized in that: The diode comprises an anode layer, a hole injection layer, at least one hole transport layer, a light emitting layer, at least one electron transport layer, an electron injection layer and a cathode layer which are stacked in sequence.
10. The organic light emitting diode according to claim 9, characterized in that: The mass percentage of the narrow-band violet light material in the luminescent layer is 0.1% to 20%. The thickness of the light-emitting layer is 10 nm to 200 nm.
11. Use of the narrow-band violet material according to any one of claims 1 to 6 in electroluminescence.
Citation Information
Patent Citations
Luminescent layer material, organic electroluminescent device and electronic equipment
CN114195794A
Multi-resonance micromolecular luminescent material and organic electroluminescent diode
CN114853767A
MR-HLCT near ultraviolet luminescent material and application thereof in OLEDs
CN115850317A
Organic electroluminescent materials and devices
CN117956823A
